ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROBABILITAS FINANCIAL DISTRESS PERBANKAN INDONESIA - Choirina, Putri Mutia; Afri Yuyetta, Etna Nur (Diponegoro Journal of Accounting, 2015)
This research aims to analyze the effect of the variabels to predict Indonesian Banks’s financial distress. Those variabel was chosen by using 5C methods. The 5C methods consist of GCG (good corporate governance), NCF (net cash flow), CIR (cost income ratio), LDR (loan to deposit ratio), ETA (equity capital to total asset), TAG (total asset growth), NPL (non performing loans), PE (price to earning ratio), PB (price to book ratio). The population of this study was all banks listed in Indonesia Stock Exchange (ISX) in 2008-2013. Sampling is done by using purposive sampling method, until founded that was 25 financial distress phenomena that happens in that periods.This study used logistic regression analysis for testing the influence of independent variables on dependent variable.The results of this study showed good corporate governance, equity capital to total asset, and price to book ratio negative significantly influence to the probability of financial distress. Meanwhile price to earning ratio positive significantly influence to the probability of financial distress. Cost income ratio, loan to deposit ratio, total asset growth and non performing loans had no significantly influence to to the probability of financial distress.